Displacement as a Racial Project: Critical Race Analysis of Hazara Exclusion in The Kite Runner - Subedi, Kabita; Bisokarma, Indra Bhahadur (Cognition, 2026)
This article explores race-based displacement in Khaled Hosseini’s The Kite Runner using Critical Race Theory (CRT). This study shows how structural racism works in Afghan society at both material and symbolic levels by highlighting the racialized experiences and perceptions of Hazara characters, particularly Hassan and Sohrab. This study uses CRT ideas like racial realism, interest convergence and counter-storytelling to highlight that race in Afghanistan is socially constructed way to control people, not a biological fact. The novel’s portrayal of the Pashtun-Hazara divide demonstrates how the minorities are pushed to the side, silenced and compelled to move to other places. This study, in addition critiques the concept of color-blindness that tends to erase visibility of racial differences and imposes systematic inequalities. Moreover, this article finds that the idea of racism sustains itself through politics and narratives that show how it happens through institutional violence, social betrayal and cultural exclusion.